Language Politeness in Students' Thesis Guidance - Aidil Syah Putra; Yumna Rasyid; Fathiaty Murtadho (UNIB Press, 2023)
This study aims to gain an in-depth understanding of the phenomenon of Language Politeness in Student Thesis Guidance of students of the English Education Study Program, FKIP University of Muhammadiyah Tangerang. The design of this research is qualitative with phenomenological methods. The data in this study were obtained through recorded speech acts and semistructured interviews with 29 students from Sundanese, Javanese, Betawi and Minang ethnic groups. The results showed that there were 10 forms of acts of courtesy of students, namely the form of praise, orders, requests, approval, giving, invitations, rejection, expressions of gratitude, sympathy, and acceptance speech. Furthermore, the politeness phenomenon that occurs in college student speech is motivated by several factors, i.e., the use of vocabulary, grammar, and direct-indirect sentences, which in turn affect the different views of college students about politeness which are motivated by the culture and environment where they live, the habits of the way of speaking they use in speech, their understanding of the context of speech.